Ruby gobble's remembrances - Veit, Kathy (Cimarron, New Mexico Cimarron Legend, 1992)
Article on the remembrances of Ruby Gobble in the Rodeo roping. Ruby Gobble and Gretchen Samis both were in the cowgirl hall of fame in the Macy's day parade in 1991.
Master List item # 8
File location is in the Raton File Cabinet
Keywords: Gobble, Ruby; Binford, Nancy; Samis, Gretchen; World ChampionTeam-Roper; World Champion Ribbon Roper; Women's Professional Rodeo Association; Tri-State Fair; Cowgirl hall of fame; Macy's Thanksgiving Parade; Chase Ranch; Local History; Rodeo; Roping; Champion; Judging; Hall of fame; Cowgirl; Cimarron, New Mexico; New York